Dispersive liquid-liquid microextraction based on solidification of floating organic drop for simultaneous separation/preconcentration of nickel, cobalt and copper prior to determination by electrothermal atomic absorption spectrometry - Mooud Amirkavei; Shayessteh Dadfarnia; Ali Mohammad Haji Shabani (Química Nova, 2013)
A dispersive liquid-liquid microextraction based on solidification of floating organic drop for simultaneous extraction of trace amounts of nickel, cobalt and copper followed by their determination with electrothermal atomic absorption spectrometry was developed. 300 µL of acetone and 1-undecanol was injected into an aqueous sample containing diethyldithiocarbamate complexes of metal ions. For a sample volume of 10 mL, enrichment factors of 277, 270 and 300 and detection limits of 1.2, 1.1 and 1 ng L-1 for nickel, cobalt and copper were obtained, respectively. The method was applied to the extraction and determination of these metals in different water samples.